Probability and random processes - G R Grimmett (Clarendon, 1997)
The book contains around 675 problems in probability and random processes, together with their solutions. The range of topics covered is broad, beginning with the elementary theory of probability and random variables, and continuing, via chapters on Markov chains and convergence, to extensive sections deveted to stationarity and ergodic theory, renewals, queues, martingales, and diffusions